ANALISIS SWOT SEBAGAI STRATEGI BANGKIT DARI KETERPURUKAN PASCA PANDEMI DILIHAT DARI KINERJA KARYAWAN DI HOTEL VILA LUMBUNG SEMINYAK - I Nyoman Suarjaya; I Made Bayu Wisnawa (Universitas Triatma Mulya, 2023)
This study is aimed at conducting an in-depth analysis of both internal and external factorsthat have an impact on the strategy for overcoming adversity post-pandemic, focusing on theperformance of employees at Hotel Villa Lumbung Seminyak using a SWOT analysis framework. The findings of this research highlight that there are promising opportunities and strengths within Hotel Villa Lumbung Seminyak that can be harnessed to formulate effective strategies for emerging stronger from the challenges posed by the pandemic. However, it is imperative to address certain pressing threats promptly.One immediate concern is related to the compensation packages and promotion structures offered to the employees. Ensuring that the remuneration is competitive and commensurate with industry standards can help in retaining and motivating talented staff. Additionally, providing clear pathways for career advancement can boost morale and enhance performance. Furthermore, the hotel's development plans should be carefully aligned with their workforce's performance. Any changes or expansion initiatives should be carried out in a way that supports and nurtures the capabilities and well-being of the employees. This holistic approach will not only contribute to achieving the hotel's goal of bouncing back from the pandemic's impact but also foster a conducive work environment. In conclusion, the SWOT analysis indicates that Hotel Villa Lumbung Seminyak possesses the potential to devise and implement effective strategies for recovery and growth in the post-pandemic era. By addressing the identified threats and capitalizing on their strengths and opportunities, the hotel can work towards a resilient and prosperous future.